Brotherband : The Ghostfaces - Book 6 - Flanagan, John (John Anthony) (New York : Philomel Books, 2016)
When a massive storm at sea blows the Brotherband crew off course to a land so far west Hal cannot recognize it from his maps, they face an unknown enemy.
Keywords: Seafaring life -- Juvenile fiction; Adventure stories; Pirates -- Juvenile fiction; Friendship -- Juvenile fiction; Courage -- Juvenile fiction; Seafaring life -- Fiction; Adventure and adventurers -- Fiction; Pirates -- Fiction; Friendship -- Fiction; Courage -- Fiction; Fantasy; Fantasy fiction